2009
DOI: 10.1007/s00535-008-2282-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare pancreatic neoplasms: the utility of endoscopic ultrasound-guided fine-needle aspiration—a large single center study

Abstract: Pancreatic neoplasms other than ductal adenocarcinomas have diverse imaging and histopathological features. EUS-FNA is accurate and safe for their identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…A recent Japanese study (36) reviewed 455 pancreatic FNA procedures: 28 were rare pancreatic tumors (no ductal adenocarcinomas). EUS-FNA with cytology, cellblock, and immunocytochemistry correctly diagnosed tumor type in 19 patients 19 (68%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Japanese study (36) reviewed 455 pancreatic FNA procedures: 28 were rare pancreatic tumors (no ductal adenocarcinomas). EUS-FNA with cytology, cellblock, and immunocytochemistry correctly diagnosed tumor type in 19 patients 19 (68%).…”
Section: Discussionmentioning
confidence: 99%
“…The present authors and our colleagues previously reported that the cytology was more accurate than histopathology in EUS‐FNA for the differential diagnosis of pancreatic mass lesions 10 . However, the usefulness of histopathology combined with immunohistochemical analysis to determine specific etiology has been reported 9 . Thus, a system in which both cytology and histopathology are available, needs to be developed.…”
Section: Eus‐fnamentioning
confidence: 85%
“…Recently, the utility of EUS‐FNA making an etiological diagnoses has been reported. Examples include characterization of histological subtypes of rare forms of pancreatic cancer, 9 inflammatory pancreatic mass 10 or autoimmune pancreatitis, 11,12 gastrointestinal stromal tumor (GIST), 13,14 subtypes of malignant lymphoma, 15 sarcoidosis and so on. Such diagnoses are based on one or more of histological (H&E staining), immunohistochemical or genetic analysis.…”
Section: Eus‐fnamentioning
confidence: 99%
“…In their study on atypical lesions, Evan et al identified pancreatic lymphomas in 5% of their samples, benign lesions in 11% and pancreatic ductal carcinomas in 21% . Similar to the cytological diagnoses of tumours of the breast and thyroid gland and based on the Bethesda system, the cytological and histological diagnosis of pancreatic specimens should be performed while receiving constructive feedback with the possibility of re‐examination …”
Section: Discussionmentioning
confidence: 99%